Determinan Stres Kerja, Kompensasi, dan Lingkungan Kerja Terhadap Kepuasan Kerja PT. Gunawan Nganjuk - Basthoumi Muslih; Araya Eka Putra (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2022)
The current unstable economic conditions force entrepreneurs to survive and live on in managing and maintaining their businesses. The role of human resources is very important in a company. Human resources in question are people who provide energy, thoughts, talents, creativity, and business in carrying out company activities. The approach in this study uses a quantitative approach with causal research techniques. Collecting data by distributing questionnaires. The population in this study were all employees of PT. Gunawan. The sample used is 40 respondents. The sampling technique used the accidental sampling technique. The data analysis technique used multiple linear regression analysis with the help of SPSS software for windows version 23. The conclusions of this study are (1) Job stress has a negative effect on job satisfaction at PT. Gunawan Nganjuk. (2) Compensation affects job satisfaction at PT. Gunawan Nganjuk. (3) The work environment affects job satisfaction at PT. Gunawan Nganjuk. (4) Work stress, compensation, and work environment simultaneously affect job satisfaction at PT. Gunawan Nganjuk